ANALISA STRUKTUR DRAMATIK DALAM FILM “LION” MENGGUNAKAN KONSEP PIRAMIDA FREYTAG DAN SKEMA HUDSON - Pratama, Regiansyah (Institut Seni Budaya Indonesia Bandung, 2017)
The dramatic structure is a unified event consisting of a section containing plot elements. This series is structured and mutually preserves the story continuity from beginning to end. Structure is a unity of parts which, if any part of it is altered or damaged, will change or corrupt the whole structure. In a movie called Lion is told a 5-year-old boy named Saroo who got lost when accidentally carried by a train that took him to Calcutta, India. Movies that tell a story must have dramatic struktru, therefore film also has the essence. One example in the main character Lion film does not easily solve the problem but he has to fight first to get to the final destination. Such is the dramatic structure, bringing the audience into the soul of the main character, in order to feel and follow the story from beginning to end.